Effect of self-management and cognitive restructuring on substance abuse among in-school adolescents with hearing impairment In Ibadan, Oyo State, Nigeria (2020)
This study examined the effect of self-management and cognitive restructuring strategies on substance abuse among in-school adolescents with hearing impairment in Ibadan, Oyo State, Nigeria. The pretest posttest control group quasi-experimental research design with 3x2 factorial matrix was adopted for the study. The sample comprised 30 male and female adolescents with hearing impairment selected from three secondary schools in Ibadan. The purposive sampling technique was used to select the schools and sample for the study. Four instruments: were used for data collection. They include short drug screening instrument (SSD), sample screening instrument (SSI), self-management strategy training package and cognitive restructuring strategy package. Data collected were analysed using Analysis of Covariance and Scheffe Post hoc Analysis at 0.05 level of significance. There was significant main effect of treatment in reduction of substance abuse among adolescents with hearing impairment f (2.27) =6.430, P<0.05, η2=.527 and there was significant interaction effect of treatment and socio-economic status on substance abuse among adolescents with hearing impairment. Based on the findings, self-management and cognitive restructuring strategies should be adopted in reducing substance above among adolescents with hearing impairment and parents should not neglect their children with hearing impairment. The schools should ensure that counseling services are put in place in order to discourage substance abuse among adolescents with hearing impairment.